2006
DOI: 10.1243/095441105x63291
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of clinically relevant wear particles from metal-on-metal hip prostheses

Abstract: The problems of osteolysis and late aseptic loosening associated with ultra-high molecular weight polyethylene (UHMWPE) particles has lead to a renewed interest in metal-on-metal prostheses. Wear particles generated by modern Co-Cr-on-Co-Cr prostheses are nanometre in size (range: 10-120 nm; mean: about 40 nm), an order of magnitude smaller than the size of UHMWPE known to be critical for activation of osteolytic cytokines by macrophages. Co-Cr wear particles will induce osteolytic cytokine production by human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 76 publications
2
44
0
Order By: Relevance
“…Elevated chromium and cobalt levels have been found in both the serum and remote organs of patients with metal-on-metal bearings [1,2,10]. Studies have also demonstrated excessive wear with onepiece metal shells in women with smaller diameter components as well as in hips in which the shell is oriented more vertically in the pelvis (a higher abduction angle) [5,11,13,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated chromium and cobalt levels have been found in both the serum and remote organs of patients with metal-on-metal bearings [1,2,10]. Studies have also demonstrated excessive wear with onepiece metal shells in women with smaller diameter components as well as in hips in which the shell is oriented more vertically in the pelvis (a higher abduction angle) [5,11,13,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ions can be generated from not only corrosion but also repassivation, modular components, delaminated metal coatings, impingement, and fixation screws [24,30]. Although metal ions disseminate throughout the reticuloendothelial system at less than toxic levels [1,8], metal particles can concentrate locally in the periprosthetic soft tissue [16] causing metallosis [9] and frank tissue necrosis [3]. Histologic studies of MoM periprosthetic tissue have identified a characteristic pattern of DLI in the inner neocapsular layer and PVLI in the intermediate vascular layer [39,40] suggestive of a DTH reaction.…”
Section: Discussionmentioning
confidence: 99%
“…MoP implants generally produce a higher volume of wear particles than MoM implants, but the latter generate a larger number of particles, as metal particles are an order of magnitude smaller [55][56][57][58][59]. The adaptive immune system reacts differently to MoM and MoP implants: unlike MoM implants, a specific cell-mediated response to ultrahigh molecular weight polyethylene (UHMWP) does not appear to play a major role in MoP implant loosening.…”
Section: Orthopedic Implantsmentioning
confidence: 99%